Reproducing honor: Child marriage within symbolic and communal power relations in East Kalimantan - Sri Murlianti; Ahmad Hidayah; Aji Eka Qamara Yulianti Dewi Hakim; Irza Mahendra; Rayhan Sayyidan Malik; Abdul Halim Ali (JURNAL ILMU SOSIAL, 2025)
Child marriage remains a persistent social practice within Indonesian society, including in East Kalimantan, a region marked by strong extractive economic structures, pronounced spatial inequalities, and rapid social transformations as a buffer zone for the new national capital (IKN). This article examines child marriage practices across 13 districts and municipalities in East Kalimantan through Pierre Bourdieu’s theory of social practice, emphasizing the interplay between habitus, symbolic capital, and social fields in shaping social action. The study employs a descriptive-qualitative method, based on in-depth interviews with 89 individuals engaged in Child marriage. Findings reveal that Child marriage is legitimized by communal moral pressures, customary norms, and the logic of family honor, further reinforced by the state through marriage dispensation practices in religious courts. The agency of adolescent girls in decision-making is severely constrained by patriarchal social structures, structural poverty, and limited access to education and reproductive health services. Within a social space characterized by unequal distribution of cultural and symbolic capital, Child marriage emerges as a strategy of honor reproduction deemed socially legitimate. The article argues that child marriage is not merely an individual problem but a product of symbolic power relations and local social structures. Reform of marriage dispensation regulations, community-based sexuality education, and value interventions through grassroots institutions are urgently needed to disrupt the cycle of intergenerational inequality.